2019
DOI: 10.3390/atmos10080460
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Atmospheric Turbulence Characteristics by the Ultrasonic Anemometers and the Calibration Processes

Abstract: In ultrasonic equipment (anemometers and thermometers), for the measurement of parameters of atmospheric turbulence, a standard algorithm that calculates parameters from temporary structural functions constructed on the registered data is usually used. The algorithm is based on the Kolmogorov–Obukhov law. The experience of using ultrasonic meters shows that such an approach can lead to significant errors. Therefore, an improved algorithm for calculating the parameters is developed, which allows more accurate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 9 publications
1
15
0
3
Order By: Relevance
“…Calculations have enabled quantitative estimates of changes of the optical turbulence. Furthermore, we plan to use an improved algorithm [4] to calculate the statistics of turbulent characteristics. Increased accuracy is ensured by taking into account the shape of the turbulence spectrum at low frequencies.This will allow a detailed study of the structure of atmospheric flows and energy exchange between large and small scales in rough terrain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations have enabled quantitative estimates of changes of the optical turbulence. Furthermore, we plan to use an improved algorithm [4] to calculate the statistics of turbulent characteristics. Increased accuracy is ensured by taking into account the shape of the turbulence spectrum at low frequencies.This will allow a detailed study of the structure of atmospheric flows and energy exchange between large and small scales in rough terrain.…”
Section: Discussionmentioning
confidence: 99%
“…To study the atmospheric turbulence, large scale air motions, temporal variations of the mean meteorological characteristics, the data of ultrasonic anemometers are widely used [4][5][6][7][8].The results of a field intercomparison experiment of a number of sonic anemometer models point to biases in the measured characteristics. However, biases are generally very small for these sensors [9].…”
Section: The Repeatability Of the Optical Turbulence At The Baykal Asmentioning
confidence: 99%
“…Among the available instruments to measure atmospheric turbulent wind, sonic anemometry (ultrasound pulse based) is a widely used and well-established technique (Cuerva and Sanz-Andrés, 2000;Kaimal, 1979;Nosov et al, 2019). The time ∆t, for an acoustic signal to travel the distance s between the transceivers of the anemometer is measured, yielding ∆t = s/(c + u), where c is the sound speed and u the wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…Other limitations include line averaging effects and transducer shadows, which are well known and studied and accounted for (Cuerva and Sanz-Andrés, 2000;Wyngaard et al, 1985).The optimal configuration of the sensors, as developed by Kaimal (1979), greatly overcomes the limitations of sonic anemometry when compared to other types of sensors (Cuerva and Sanz-Andrés, 2000). Sonic Anemometers are able to measure instantaneous 3D velocity components with a high sample rate up to 100 Hz, without the need of moving parts interfering with the flow (as with a cup anemometer, for example) and with negligible effects of the design features (Nosov et al, 2019). They show a linear response, with calibration parameters which stay fixed after setup (Cuerva and Sanz-Andrés, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates the implementation of 3D sonic anemometers arrayed in a way to do what each sonic anemometer was originally designed to do best: acoustically interrogate eddies and sense temperature, moisture, and wind velocity (and hence pressure) gradients, which, in combination, lead to index of refraction gradients. Nosov et al [5] have similarly demonstrated a calibrated method to obtain C 2 T , C 2 v , and C 2 n from a small array of ultrasonic anemometers. This paper extends the relationships shown in [5] with evidence demonstrating optical turbulence strength, C 2 n , can be derived from a parameter, C 2 v , which is more directly tied to the turbulent eddy distribution independent of non-adiabatic temperature gradients that many techniques tend to exploit to their advantage, but that can disappear when turbulence does not.…”
Section: Introductionmentioning
confidence: 99%